CD4 T Cells but Not Th17 Cells Are Required for Mouse Lung Transplant Obliterative Bronchiolitis. Issue 7 (13th March 2015) - Wu, Q.; Gupta, P. K.; Suzuki, H.; Wagner, S. R.; Zhang, C.; Cummings, O. W.; Fan, L.; Kaplan, M. H.; Wilkes, D. S.; Shilling, R. A.
<x xml:space="preserve">Abstract</x> Lung transplant survival is limited by obliterative bronchiolitis (OB), but the mechanisms of OB development are unknown. Previous studies in a mouse model of orthotopic lung transplantation suggested a requirement for IL‐17. We have used this orthotopic mouse model to investigate the source of IL‐17A and the requirement for T cells producing IL‐17A. The major sources of IL‐17A were CD4+ T cells and γδ T cells. Depletion of CD4+ T cells led to a significantly decreased frequency and number of IL‐17A+ lymphocytes and was sufficient to prevent acute rejection and OB. However, mice with STAT3‐deficient T cells, which are unable to differentiate into Th17 cells, rejected lung allografts and developed OB similar to control mice. The frequency of IL‐17A+ cells was not decreased in mice with STAT3‐deficient T cells due mainly to the presence of IL‐17A+ γδ T cells. Deficiency of γδ T cells also did not affect the development of airway fibrosis. Our data suggest that CD4+ T cells are required for OB development and expansion of IL‐17A responses in the lung, while Th17 and γδ T cells are not absolutely required and may compensate for each other.